INHERITANCE PATTERNS OF INTERFAITH FAMILIES IN PEKALONGAN REGENCY - Yusron, Muhammad; Alfaraby, Mu'taz Ramadhan (Indonesian Journal of Shariah and Justice, 2025)
Interfaith families are one of the social phenomena that often give rise to problems, including inheritance problems. Inheritance becomes a problem that arises because the status of legal subjects of different religions has implications for the inability to apply Islamic inheritance rules, both those contained in the Compilation of Islamic Law and classical fiqh because religious differences are considered a barrier to inheritance. This article examines inheritance practices among interfaith families in Pekalongan Regency. The focus of this study is to explore and explore inheritance patterns of interfaith families in Pekalongan Regency and the factors behind the formation of these inheritance patterns. This study is an empirical legal study with a socio-legal approach. The results of the study state that the distribution of inheritance in interfaith families in Pekalongan Regency uses an equal distribution system without distinguishing between gender or religion of the decedent or heirs. The factors behind the practice of inheritance distribution are: factors of public interest and harmony between families; factors of local customs, traditions, and culture; factors of community beliefs in religious life; and factors of the meaning of justice. These factors reflect the existence of instrumental rationality, rational actions based on values that are believed in, affective actions that are dominated by emotions, and traditional actions that focus on the experiences of their ancestors in inheritance distribution practices.